IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) DI LINGKUNGAN SMA PEWARIS PERADABAN PLUS - Setiawati Setiawati; Ichwani Siti Utami; Abi Robian (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
Abstract The School Literacy Movement (GLS) is a massive and structured movement to foster the habits and abilities of students to be able to access, understand, and use something intelligently through various activities, including reading, seeing, listening, writing, speaking and being able to utilize and implement what they know in everyday life. The School Literacy Movement (GLS) is considered effective if students master six basic literacy, namely (1) language literacy, (2) numeracy literacy, (3) scientific literacy, (4) digital literacy, (5) financial literacy, and (6) cultural and civic literacy. The title of the study is